Economic analysis of opportunities to accelerate Alzheimer's disease research and development. (27th March 2014) - Scott, Troy J.; O'Connor, Alan C.; Link, Albert N.; Beaulieu, Travis J.
Abstract : The development of disease‐modifying treatments for Alzheimer's disease (AD) faces a number of barriers. Among these are the lack of surrogate biomarkers, the exceptional size and duration of clinical trials, difficulties in identifying appropriate populations for clinical trials, and the limitations of monotherapies in addressing such a complex multifactorial disease. This study sets out to first estimate the consequent impact on the expected cost of developing disease‐modifying treatments for AD and then to estimate the potential benefits of bringing together industry, academic, and government stakeholders to co‐invest in, for example, developing better biomarkers and cognitive assessment tools, building out advanced registries and clinical trial‐readiness cohorts, and establishing clinical trial platforms to investigate combinations of candidate drugs and biomarkers from the portfolios of multiple companies. Estimates based on interviews with experts on AD research and development suggest that the cost of one new drug is now 5.7 billion (95% confidence interval (CI) 3.7–9.5 billion) and could be reduced to 2.0 billion (95% CI 1.5–2.9 billion). The associated acceleration in the arrival of disease‐modifying treatments could reduce the number of case years of dementia by 7.0 million (95% CI 4.4–9.4 million) in the United States from 2025 through 2040.